Integrasi Tantangan dan Strategi Digitalisasi Pelayanan Publik: Kajian Literatur - Irsad Munawir; Pandu Pamungkas; Rindy Putri Hapsari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
Digital transformation in public service delivery has become a strategic agenda in Indonesia, yet its implementation continues to face complex challenges. This study aims to comprehensively identify and integrate the challenges and strategies of public service digitalization. A library research method with descriptive comparative analysis was applied to scientific literature, regulations, and policy reports from 2022-2026. The findings reveal four primary challenges: the digital infrastructure gap between urban and rural areas, low digital competency among civil servants (ASN) coupled with high vendor dependency, regulatory fragmentation generating inter agency digital silos, and low digital literacy among vulnerable groups. Strategies developed in response include strengthening SPBE policy, building human resource capacity through National Digital Literacy Movement, fostering multi stakeholder collaboration through regional platform innovations, and implementing community based inclusive digital education. The integration framework indicates that regulatory fragmentation is the root cause determining the effectiveness of all other dimensions. This study concludes that a fundamental paradigm shift from output oriented to outcome oriented approaches, supported by holistic, adaptive, and cross sectoral strategies, is essential for effective and inclusive digitalization.